Perfect phrases for virtual teamwork : hundreds of ready-to-use phrases for fostering collaboration at a distance - Runion, Meryl (Perfect phrases series., 2012)
With more and more employees working offsite, effective communication among remote team members is absolutely critical. Perfect Phrases for Virtual Teamwork provides hundreds of ready-to-use phrases that will ensure your virtual teams collaborate as effectively as the most cohesive face-to-face team.